Implant-abutment screw removal torque values between customized titanium abutment, straight titanium abutment, and hybrid zirconia abutment after a million cyclic loading: an in vitro comparative study - Disayut Klongbunjit; Weerapan Aunmeungtong; Pathawee Khongkhunthian (SpringerOpen, 2021)
Abstract Purpose The aim of this study was to compare removal torque values after mechanical cyclic loading and bending moment after the static compression testing of customized titanium abutment compared with prefabricated and hybrid abutments. Materials and methods The study was developed according to ISO 14801:2016. Sixty implants were divided into three groups equally: Straight titanium abutment group, Customized titanium abutment group, and Hybrid zirconia abutment group. Abutments were fabricated with zirconia restoration. Forty five implants underwent for cyclic loading. The removal torque values were measured after a fatigue test was conducted at 0 cycles (control), 50,000 cycles and 1,000,000 cycles. In the second experiment, 15 implants were divided into the same groups. Then, bending moments were investigated. Results The mean initial removal torque value was significantly higher than 50,000 cycles and 1,000,000 cycles (P < 0.001). The comparison of mean removal torque value between types of abutments was not significantly different (P > 0.05), and the bending moments of all abutments were not significantly different (P > 0.05). Conclusions From the boundary of this in-vitro study, it could be concluded that customized titanium abutment and hybrid abutment were not significantly different in terms of removal torque values after the fatigue test. The bending moment between types of abutment were not significantly different. Thus, it could be concluded that abutment type does not significantly influence abutment stability or fracture strength.